Unveiling cultural intelligence: A comparative study of Japanese and Indonesian idiomatic expressions - Agus Suherman Suryadimulya; Reiza D. Dienaputra; Awaludin Nugraha; Susi Machdalena; Nyai Kartika (Universitas Pendidikan Indonesia, 2023)
This paper delves into the realm of cultural intelligence inherent in Japanese and Indonesian idiomatic expressions. In the context of intercultural communication, Indonesian speakers utilize diverse cultural intelligence frameworks to express various facets of Japanese culture, with language serving as a prominent component. While a plethora of studies have examined idioms from semantic and semiotic perspectives, a notable gap exists in the literature regarding the exploration of cultural intelligence within idiomatic expressions in both languages, encompassing both structural and semantic analyses. Filling this research void, the present study aims to elucidate the concept of cultural intelligence, specifically focusing on the comprehension of Japanese and Indonesian idioms, particularly those related to the notion of